Molecular Docking-Based Screening of Phytochemicals from Dimocarpus longan Lour. Peel Extract as Potential Larvicidal Agents Against Aedes aegypti - Mardhah Sasri Utami; Ivone Lutfiyah; Amalia Shari (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2026)
Dengue fever continues to threaten global health, especially in tropical regions where Aedes aegypti mosquitoes proliferate. Ideally, vector populations would be controlled with environmentally safe, effective larvicides. In reality, chemical insecticides like temephos raise concerns about resistance, environmental toxicity, and non-target effects. To address these issues, this study evaluated bioactive compounds from longan peel (Dimocarpus longan Lour.) as potential natural larvicides. Thirteen phytochemicals were screened for drug-likeness, toxicity, and aqueous solubility, selecting three compounds with favorable properties. These were docked against 3-HKT, a critical enzyme for larval survival, using AutoDock Vina in PyRx 0.8, with temephos as a reference. Ligand-protein interactions and complex flexibility were analyzed using BIOVIA Discovery Studio and CABS-flex 2.0. Results indicated that epicatechin, 4-O-methylgallic acid, and ethyl gallate exhibited stronger binding affinities than temephos. These findings indicate that phenolic and flavonoid compounds from longan peel can target 3-HKT and may support sustainable mosquito control. These findings highlight the urgency of eco-friendly larvicide development and provide a molecular basis for further in vitro and in vivo validation against Aedes aegypti larvae.